(untitled) - Đặng Ngọc Tú (Tp. HCM, 2000)
Sách gồm nhiều kiểu bài tập với những đáp án rất thuận tiện cho việc tự học, tự kiểm tra kết quả học tập
Keywords: english language - glossaries, vocabularies, etc,english language - study and teaching,english language - textbooks for foreign speakers,vocabulary